Randomized Comparison of Renal Denervation Versus Intensified Pharmacotherapy Including Spironolactone in True-Resistant Hypertension: Six-Month Results From the Prague-15 Study. Issue 2 (February 2015) - Rosa, Ján; Widimský, Petr; Toušek, Petr; Petrák, Ondřej; Čurila, Karol; Waldauf, Petr; Bednář, František; Zelinka, Tomáš; Holaj, Robert; Štrauch, Branislav; Šomlóová, Zuzana; Táborský, Miloš; et al.
Abstract : This prospective, randomized, open-label multicenter trial evaluated the efficacy of catheter-based renal denervation (Symplicity, Medtronic) versus intensified pharmacological treatment including spironolactone (if tolerated) in patients with true-resistant hypertension. This was confirmed by 24-hour ambulatory blood pressure monitoring after excluding secondary hypertension and confirmation of adherence to therapy by measurement of plasma antihypertensive drug levels before enrollment. One-hundred six patients were randomized to renal denervation (n=52), or intensified pharmacological treatment (n=54) with baseline systolic blood pressure of 159±17 and 155±17 mm Hg and average number of drugs 5.1 and 5.4, respectively. A significant reduction in 24-hour average systolic blood pressure after 6 months (−8.6 [95% cofidence interval: −11.8, −5.3] mm Hg; P <0.001 in renal denervation versus −8.1 [95% cofidence interval: −12.7, −3.4] mm Hg; P =0.001 in pharmacological group) was observed, which was comparable in both groups. Similarly, a significant reduction in systolic office blood pressure (−12.4 [95% cofidence interval: −17.0, −7.8] mm Hg; P <0.001 in renal denervation versus −14.3 [95% cofidence interval: −19.7, −8.9] mm Hg; P <0.001 in pharmacological group) was present. Between-group differences in change were not significant. The average number of antihypertensive drugs used after 6 months was significantly higher in the pharmacological group (+0.3 drugs; P <0.001). A significant increase in serum creatinine and a parallel decrease of creatinine clearance were observed in the pharmacological group; between-group difference were borderline significant. The 6-month results of this study confirmed the safety of renal denervation. In conclusion, renal denervation achieved reduction of blood pressure comparable with intensified pharmacotherapy. Abstract : Supplemental Digital Content is available in the text.